Mirrors of Modernity: Time–Space, the Subaltern, and the Decolonial. Issue 1 (2nd January 2016) - Dube, Saurabh
Abstract : This essay is cast as something of a personal narrative. It recounts how I have arrived at inklings and intimations of space and time, particularly pervasive procedures of the spatialization of time and the temporalization of space, in tandem with understandings of disciplines and subjects of modernity. The account begins with my pre-apprentice days in Delhi, moves onto my apprenticeship at Cambridge, covers my journeyman sojourns in Mexico, and extends unto my artisanal concerns in the present. At stake especially are encounters and entanglements with time and space as folded within the creases of subaltern studies and de-colonial understandings (yet also postcolonial perspectives and historical anthropology). On the one hand, I explore how these shifting orientations have drawn upon hegemonic representations as well as non-certified imaginations of time and space, to now press familiar associations and now unravel unusual enunciations of these concepts and processes. On the other hand, I track the active construal, the exact production, of space and time within the epistemic practice of these critical perspectives. At stake throughout are wider issues of meaning and power, alterity and authority, difference and disciplines.